Macroscale superlubricity of steel by polymer-based ionic liquids without a running-in period. (April 2023) - Chen, Huanyi; Cai, Tao; Li, Hua; Ruan, Xinxin; Jiao, Chengcheng; Atkin, Rob; Wang, Yandong; Gong, Ping; Zhou, Xiangyang; Yu, Jinhong; Jiang, Nan
Abstract: A series of polymer-based ionic liquids (PILs) with a flexible and electron-rich polymeric chain attached to the cation have been designed as lubricants for steel-steel systems. Compared to widely used poly-alpha olefin (PAO) and commercial lubricants, the PIL lubricants show noticeably lower friction and better surface protection. Notably, for the PIL, ionic liquids based on 2, 5-furandicarboxylic acid (FA-IL), macroscale superlubricity is achieved immediately (without a running-in period) when the temperature is 75 °C and higher. Surface characterizations and molecular dynamics simulations show superlubricity results from the robust lubricating film immediately formed at the steel surface due to the rapid adsorption of FA-IL ions via multiple sites. This work provides new insights into the design of macroscale superlubricity systems. Graphical Abstract: ga1 Highlights: PILs are designed to improve lubricity in a rigid-flexible manner based on a high-fluidity polymer and rigid ring. Compared to commercial lubricants, PIL lubricants show noticeably lower friction and better surface protection. Designed ionic liquid FA-IL achieving macroscale superlubricity on industrial steel surfaces without a run-in period. The rapid adsorptions of FA-IL to the steel surface via multiple sites form a robust lubricating film at the interface.